2016
DOI: 10.7759/cureus.927
|View full text |Cite
|
Sign up to set email alerts
|

The Human Central Canal of the Spinal Cord: A Comprehensive Review of its Anatomy, Embryology, Molecular Development, Variants, and Pathology

Abstract: The human central canal of the spinal cord is often overlooked. However, with advancements in imaging quality, this structure can be visualized in more detail than ever before. Therefore, a timely review of this part of the cord seemed warranted. Using standard search engines, a literature review was performed for the development, anatomy, and pathology involving the central canal. Clinicians who treat patients with issues near the spine or interpret imaging of the spinal cord should be familiar with the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Dorsal outlets for the fluid in the CC with connections from the filum terminale internum to the SAS have been identified in the sacral spine in rats, rabbits, guinea pigs, and rhesus monkeys (Leduc et al, 1956; Bradbury and Lathem, 1965; Nakayama, 1976). In humans, a normal flow within this anatomic space is often paid little heed, as it is believed that CC is occluded after the third decade of life (Saker et al, 2016). This is despite the well-known association between dilated CCs and the development of syringomyelia (Gardner and Goodall, 1950; Williams and Bentley, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Dorsal outlets for the fluid in the CC with connections from the filum terminale internum to the SAS have been identified in the sacral spine in rats, rabbits, guinea pigs, and rhesus monkeys (Leduc et al, 1956; Bradbury and Lathem, 1965; Nakayama, 1976). In humans, a normal flow within this anatomic space is often paid little heed, as it is believed that CC is occluded after the third decade of life (Saker et al, 2016). This is despite the well-known association between dilated CCs and the development of syringomyelia (Gardner and Goodall, 1950; Williams and Bentley, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…When knock-in mouse targeted to the mouse FoxJ1 locus was used, the differentiation potential of SCEp cells was shown to be extremely limited (Ren et al, 2017). This discrepancy may be attributable to the differences between species regarding the cytoarchitecture of progenitor cell niche or the function of NSCs or neural progenitor cells (Alfaro-Cervello et al, 2012Chandran et al, 2004;Garcia-Ovejero et al, 2015;Hamilton et al, 2009;Saker et al, 2016). This discrepancy may be attributable to the differences between species regarding the cytoarchitecture of progenitor cell niche or the function of NSCs or neural progenitor cells (Alfaro-Cervello et al, 2012Chandran et al, 2004;Garcia-Ovejero et al, 2015;Hamilton et al, 2009;Saker et al, 2016).…”
Section: Differentiation Potential Of Scep Cellsmentioning
confidence: 99%
“…Indeed, human GFAP promoter enables more broader expression, where GFAP-negative neural progenitor cells express the reporter gene in addition to GFAP-positive mature astrocytes (Andrae et al, 2001;Casper & Mccarthy, 2006;Malatesta, Hartfuss, & Gotz, 2000;Malatesta et al, 2003). This discrepancy may be attributable to the differences between species regarding the cytoarchitecture of progenitor cell niche or the function of NSCs or neural progenitor cells (Alfaro-Cervello et al, 2012Chandran et al, 2004;Garcia-Ovejero et al, 2015;Hamilton et al, 2009;Saker et al, 2016). Even in the very rare case, we observed the data suggesting astrocyte differentiation of a SCEp cell in the intact condition (Figure 3b and Supporting Information Figure S1b), but other studies concluded that it is unlikely.…”
Section: Proliferation Of Scep Cellsmentioning
confidence: 99%
“…The rostral and caudal ends close off on embryonic days 25 and 27, respectively, whereby the neural canal becomes the ventricular system. Further neural tube thickening decreases the size of the neural canal until the central canal of the spinal cord is minute 33 . A single layer of columnar ependymal cells comprise the wall of the neural tube, and during development give rise to all neural tissue in the spinal cord through neuroblast and glioblast formation 32 .…”
Section: Anatomymentioning
confidence: 99%
“…The central canal has long been thought to be completely eliminated by adulthood 38,39 through a gradual closing off of the CSF-containing tube 40 via occlusion by ependymal cell debris 30,31,41 . It remains open and relatively unobstructed until the second decade of life 33 . The majority of the central canal is elliptical 42 , although variations exist including dilations, outpouches and forkings 43,44 .…”
Section: Anatomymentioning
confidence: 99%